2008
DOI: 10.1007/978-3-540-85988-8_112
|View full text |Cite
|
Sign up to set email alerts
|

A Symmetry-Based Method for the Determination of Vertebral Rotation in 3D

Abstract: Abstract. In the past, a number of methods were proposed for quantitative assessment of vertebral rotation from three-dimensional (3D) images. However, these methods were based on manual identification of distinctive anatomical landmarks, required manual determination of cross-sections from 3D images, and measured only axial vertebral rotation instead of the rotation in 3D. In this paper, we propose an automated method for quantitative assessment of vertebral rotation in 3D that is based on finding the planes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The reported intermethod variability between their symmetry ratio algorithm and the method of Aaro and Dahlborn 9 and Ho et al 10 were 3.3 degrees and 3.4 degrees SD, respectively. The symmetry of the whole vertebral structure in 3D was proposed by Vrtovec et al, 6 who reported accuracy of 0.5 degrees and precision of 0.3 degrees after comparing each computerized AVR measurement to a single manually identified line that best described the symmetry of vertebral anatomic structures. The computerized method does, however, not search for a perfect (idealized) symmetry, but instead for the maximal available symmetry, which makes it applicable to normal as well as pathologic vertebrae.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The reported intermethod variability between their symmetry ratio algorithm and the method of Aaro and Dahlborn 9 and Ho et al 10 were 3.3 degrees and 3.4 degrees SD, respectively. The symmetry of the whole vertebral structure in 3D was proposed by Vrtovec et al, 6 who reported accuracy of 0.5 degrees and precision of 0.3 degrees after comparing each computerized AVR measurement to a single manually identified line that best described the symmetry of vertebral anatomic structures. The computerized method does, however, not search for a perfect (idealized) symmetry, but instead for the maximal available symmetry, which makes it applicable to normal as well as pathologic vertebrae.…”
Section: Discussionmentioning
confidence: 98%
“…Computerized methods do not suffer from these limitations and may yield accurate AVR results in images acquired by computed tomography (CT). [3][4][5][6] However, computerized methods also require manual identification of multiple anatomic landmarks or neglect the sagittal and coronal inclinations of vertebrae, which may result in inaccurate measurements. 7,8 The accuracy and reliability of computerized methods have not been thoroughly investigated yet.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The computerized measurements were based on a method that determines the sagittal, coronal and axial angle of vertebral rotation in 3D images from the inclination of the planes of maximal symmetry (Vrtovec et al, 2008), which divide the vertebral body into symmetrical left and right, anterior and posterior, and cephalic and caudal halves (Fig. 2).…”
Section: Computerized CVI Measurementsmentioning
confidence: 99%
“…With the increase of measurement methods, different comparisons of measurement methods appeared [7,8], in which the advantages and disadvantages of various algorithms were analyzed and the direction was pointed out for the new algorithm. Vrtovec et al [9] assessed vertebral rotation quantitatively by proposing an automated method in terms of finding the planes of vertebral symmetry. Wong et al [10] achieved the measurement vertebral rotation using 3D ultrasound method and validate the feasibility of this method.…”
Section: Introductionmentioning
confidence: 99%